2018
DOI: 10.1264/jsme2.me18058
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Production from Nitrite Reduction and Hydroxylamine Oxidation by Copper-containing Dissimilatory Nitrite Reductase (NirK) from the Aerobic Ammonia-oxidizing Archaeon, <i>Nitrososphaera viennensis</i>

Abstract: Aerobic ammonia-oxidizing archaea (AOA) play a crucial role in the global nitrogen cycle by oxidizing ammonia to nitrite, and nitric oxide (NO) is a key intermediate in AOA for sustaining aerobic ammonia oxidation activity. We herein heterologously expressed the NO-forming, copper-containing, dissimilatory nitrite reductase (NirK) from Nitrososphaera viennensis and investigated its enzymatic properties. The recombinant protein catalyzed the reduction of 15NO2− to 15NO, the oxidation of hydroxylamine (15NH2OH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 46 publications
3
40
0
1
Order By: Relevance
“…Two of the genomes (ThauP41 and ThauR71) suggest participation in nitrification; however, the most likely reason that AOA genes were not detected in ThauP25 is that this genome is not complete. The gene nirK was detected in all three genomes, indicating participation in the production of the greenhouse gas nitrous oxide, which was demonstrated by heterologous expression of nirK from Nitrososphaera viennensis [80]. The presence of genes encoding coenzyme F420 are widespread in Thaumarchaeota genomes [9,81].…”
Section: Discussionmentioning
confidence: 99%
“…Two of the genomes (ThauP41 and ThauR71) suggest participation in nitrification; however, the most likely reason that AOA genes were not detected in ThauP25 is that this genome is not complete. The gene nirK was detected in all three genomes, indicating participation in the production of the greenhouse gas nitrous oxide, which was demonstrated by heterologous expression of nirK from Nitrososphaera viennensis [80]. The presence of genes encoding coenzyme F420 are widespread in Thaumarchaeota genomes [9,81].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kobayashi et al . () demonstrated that a recombinant NirK protein from the soil thaumarchaeote Nitrososphaera viennensis was able to catalyse the production of NO from both NO 2 − reduction and NH 2 OH oxidation. This protein also produced nitrous oxide (N 2 O) from NH 2 OH and NO 2 − (Kobayashi et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In another proposed model, two molecules of NO 2 − are generated from NH 2 OH and NO, and NirK is proposed to reduce one of these NO 2 − molecules back into NO, returning it to the NO 2 − -generation module (Kozlowski et al, 2016). Recently, Kobayashi et al (2018) demonstrated that a recombinant NirK protein from the soil thaumarchaeote Nitrososphaera viennensis was able to catalyse the production of NO from both NO 2 − reduction and NH 2 OH oxidation. This protein also produced nitrous oxide (N 2 O) from NH 2 OH and NO 2 − (Kobayashi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We used cluster-specific primers because of their high detectability of diverse nirK and nirS genes. These primers represent the best potential for detecting these genes (Ma et al, 2019), but do not identify genes from archaea (Bonilla-Rosso et al, 2016;Kobayashi et al, 2018) or potentially those from some bacterial or fungal groups (Ma et al, 2019). In addition, the results on taxonomic assignment depend on the fullness of the database.…”
Section: Resultsmentioning
confidence: 99%